1986
DOI: 10.1099/0022-1317-67-5-915
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Frog Virus 3 with the Cytomatrix. IV. Phosphorylation of Vimentin Precedes the Reorganization of Intermediate Filaments around the Virus Assembly Sites

Abstract: SUMMARYFrog virus 3 (FV3) assembles in morphologically distinct assembly sites in the cytoplasm of infected cells. As the assembly sites form, the intermediate filaments (IF) aggregate, delimit the assembly sites, and remain so throughout infection. To determine the molecular basis of reorganization of IF, we analysed the vimentin of uninfected and FV3-infected cells by two-dimensional gel electrophoresis. The results showed that (i) the vimentin was more acidic in FV3-infected cells than in uninfected cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Vimentin rearrangement around virus factories has been documented for the iridovirus frog virus 3 (30). Interestingly, vimentin is phosphorylated in cells infected by frog virus 3, and a temperature-sensitive mutant of frog virus 3 that is unable to phosphorylate vimentin is unable to rearrange vimentin or initiate late gene expression (8,49). The results again point to a link between vimentin phosphorylation and rearrangement during virus infection and the control of late gene expression.…”
Section: Discussionmentioning
confidence: 47%
“…Vimentin rearrangement around virus factories has been documented for the iridovirus frog virus 3 (30). Interestingly, vimentin is phosphorylated in cells infected by frog virus 3, and a temperature-sensitive mutant of frog virus 3 that is unable to phosphorylate vimentin is unable to rearrange vimentin or initiate late gene expression (8,49). The results again point to a link between vimentin phosphorylation and rearrangement during virus infection and the control of late gene expression.…”
Section: Discussionmentioning
confidence: 47%
“…5A and 6). Indeed, several viruses, such as African swine fever virus (Carvalho et al, 1988), vaccinia virus (Ferreira et al, 1994), retrovirus (Snasel et al, 2000;Naghavi and Goff, 2007), adenovirus (Belin and Boulanger, 1987), bluetongue virus (Bhattacharya et al, 2007), frog virus 3 (Chen et al, 1986) and rotavirus (Weclewicz et al, 1994) have been reported to cause remarkable changes in intermediate filament reorganization during infection.…”
Section: Discussionmentioning
confidence: 97%
“…As seen for ASFV and poxviruses, the intermediate filament vimentin plays an important role in replication (Murti and Goorha, 1983). Vimentin is phosphorylated during FV3 infection, prior to factory formation (Chen et al, 1986;Willis et al, 1979), and temperature-sensitive mutants that are unable to phosphorylate vimentin do not form vimentin cages and are unable to proceed to late gene expression. Drug treatment with taxol or colchicine (Murti et al, 1988) showed that recruitment of vimentin to assembly sites requires dynamic, but not polymerizing microtubules, and microinjection of anti-vimentin antibody prevented recruitment of vimentin to factories.…”
Section: The Iridoviruses Generate Cytoplasmic Factories Andmentioning
confidence: 97%